Magnetic Assembly of a Multifunctional Guidance Conduit for Peripheral Nerve Repair. (5th May 2021) - Antman‐Passig, Merav; Giron, Jonathan; Karni, Moshe; Motiei, Menachem; Schori, Hadas; Shefi, Orit
Abstract: Nerve growth conduits are designed to support and promote axon regeneration following nerve injuries. Multifunctionalized conduits with combined physical and chemical cues, are a promising avenue aimed at overcoming current therapeutic barriers. However, the efficacious assembly of conduits that promote neuronal growth remains a challenge. Here, a biomimetic regenerative gel is developed, that integrates physical and chemical cues in a biocompatible "one pot reaction" strategy. The collagen gel is enriched with magnetic nanoparticles coated with nerve growth factor (NGF). Then, through a remote magnetic actuation, highly aligned fibrillar gel structure embedded with anisotropically distributed coated nanoparticles, combining multiple regenerating strategies, is obtained. The effects of the multifunctional gels are examined in vitro, and in vivo in a 10‐mm rat sciatic nerve injury model. The magneto‐based therapeutic conduits demonstrate oriented and directed axonal growth, and improve nerve regeneration in vivo. The study of multifunctional guidance scaffolds that can be implemented efficiently and remotely provides the foundation to a novel therapeutic approach to overcome current medical obstacles for nerve injuries. Abstract : Enhanced regeneration of rat peripheral nerve with a magnetically assembled multifunctional nerve growth conduit is demonstrated. The biomimicked, aligned, and growth factor releasing collagen gel is rapidly formed with magnetic assembly in a one‐pot reaction. Multifunctional gels are shown to affect axon count, axon alignment, and reconstructive tissue demonstrating nerve repair.